Smart solution for low humidity problems using automatic ultrasonic humidifier (AUH). Issue 1 (February 2021) - Sakib, Md Nazmus; Hasan Sohel, Md Mahmudul; Islam, Shahanul; Islam, Minarul
Abstract: Humidity has a substantial impact on biological and environmental factors. Improper relative humidity (too high or very low) can create discomfort for individuals and affect several systems and apparatus. On the other hand, the correct type of humidifying machinery and functions may facilitate reliable, economic, and trouble-free control of moisture. Humidity in the winter region is always too low, which causes anxiety. This study aims to develop a microcontroller-based system to identify and eliminate such low humidity problems. A control system is implemented to generate air humidity according to the need to decide whether the unit is working. A wireless sensor was used to measure the room's relative humidity and temperature. The Humidifier is activated whenever the relative humidity is less than that of the setting's value according to the standard humidity value. A humidifier is developed using vaporizing ultrasound, which can still be considered the automatic ultrasonic Humidifier (AUH). The setting is suitable in the winter zone or where the relative humidity is below the standard comfort value. In this study, data were recorded in Khulna, Bangladesh, between April and May of 2018. Most of the sensor's recorded values were greater than the standard comfort Relative humidity, so the Humidifier was disabled. Humidifier activated while the sensor recorded lower relative humidity value with comparison to the standard set value.